2019
DOI: 10.1039/c8ra10390a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of protein stability by an additional disulfide bond designed in human neuroglobin

Abstract: A disulfide bond of Cys120 and Cys15 was rationally designed in human neuroglobin (Ngb) by A15C mutation, which caused minimal structural alterations, whereas enhanced both chemical and pH stability, with a thermal stability higher than 100 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…The A15C Ngb mutant was expressed and purified as reported previously. 19 To obtain crystals for the mutant with good quality, we screened different crystallization conditions using the crystal screen reagent kits from Hampton research. We found that the mutant formed crystals suitable for X-ray diffraction with high quality (Figure 1, top-left) at 16 C within 2 weeks by using the number 23 reagent (1.6 mol/L ammonium sulfate, 0.1 mol/L 2-MES monohydrate pH 6.5, 10% v/v 1,4-dioxane).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The A15C Ngb mutant was expressed and purified as reported previously. 19 To obtain crystals for the mutant with good quality, we screened different crystallization conditions using the crystal screen reagent kits from Hampton research. We found that the mutant formed crystals suitable for X-ray diffraction with high quality (Figure 1, top-left) at 16 C within 2 weeks by using the number 23 reagent (1.6 mol/L ammonium sulfate, 0.1 mol/L 2-MES monohydrate pH 6.5, 10% v/v 1,4-dioxane).…”
Section: Resultsmentioning
confidence: 99%
“…The A15C Ngb mutant was expressed and purified as reported previously 19 . To obtain crystals for the mutant with good quality, we screened different crystallization conditions using the crystal screen reagent kits from Hampton research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, cysteine residues consider as an antioxidant defense system either directly by reacting with reactive ROS and RNS, or can be represented as cofactors for several enzymes. Additionally, cysteine residues are important modifying the structure and function of many proteins . In turn, oxidized Trx‐1 is reactivated by NADPH‐dependent flavoprotein TrxR, a homodimeric, selenium comprising flavoprotein oxidoreductase to reduce the disulfide bonds of proteins through thiol‐disulfide exchange reactions .…”
Section: Discussionmentioning
confidence: 99%
“…A disulfide bridge is the covalent bond formed by linking sulfur atoms of two spatially close cysteine residues. This type of PTM can serve either as a structural or a biochemical role by affecting protein folding, stability, and function (Creighton et al., 1995; Xiao Liu et al., 2019; Zhang et al., 2018). There are three types of disulfide bonds in cells (Cook & Hogg, 2013).…”
Section: Introductionmentioning
confidence: 99%